2009
DOI: 10.1002/jpln.200800287
|View full text |Cite
|
Sign up to set email alerts
|

A critical assessment of the suitability of phosphite as a source of phosphorus

Abstract: Marketing of phosphite-containing preparations for foliar application, together with recent reports of positive yield responses, has revived the question as to whether phosphite (HPO À 3 ) is a suitable P source for plants. Two experiments using zucchini (Cucurbita pepo L. convar. giromontina) have been conducted to evaluate the P-nutritional effect of phosphite either provided via the substrate or as a foliar spray. Plants grown in a P-deficient substrate were severely damaged when phosphite was applied as fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 30 publications
2
20
0
2
Order By: Relevance
“…There was a marked reduction in shoot and root growth in oat plants grown with Phi as the sole source of P (Figure 1a-b), which supports the view that Phi cannot replace Pi as a source of P in plants (Jost et al 2015;Ratjen and Gerendás 2009). In fact, the Phi supply was phytotoxic to oat, as suggested by the lower dry matter production in Phi plants versus Pi-D.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…There was a marked reduction in shoot and root growth in oat plants grown with Phi as the sole source of P (Figure 1a-b), which supports the view that Phi cannot replace Pi as a source of P in plants (Jost et al 2015;Ratjen and Gerendás 2009). In fact, the Phi supply was phytotoxic to oat, as suggested by the lower dry matter production in Phi plants versus Pi-D.…”
Section: Discussionsupporting
confidence: 74%
“…Phosphorus (P) in the reduced form (phosphite, Phi) cannot replace the anion phosphate (Pi) in plant metabolism, with subsequent risks of phytotoxicity and growth impairment in plants under Phi nutrition (Ratjen and Gerendás 2009;Thao et al 2008aThao et al , 2008bZambrosi, Mattos Jr., and Syvertsen. 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these effects were more severe when plants were grown in P deficient soils. Similarly, Ratjen and Gerendás (2009) found that applying phosphite to soil as a P source for zucchini cultivation caused phytotoxicity, which inhibited the formation of flowers and fruits. In this study, strawberry performance decreased with increasing concentrations of phosphite in the nutrient solution from 30% P as Phi on, though the performance between treatments was not significantly different from the control (Figure 2A).…”
Section: Yield and Fruit Sizementioning
confidence: 98%
“…Phosphite is more soluble than phosphate, which gives it greater mobility in aquatic environments [14]. Moreover, as a reduced form with relative thermodynamic instability [14], phosphite can be oxidized to phosphate or reduced to gaseous phosphine (PH 3 , À3) [8,13,15,16]. As reduction from phosphate is energetically unfeasible, unless phosphite or hypophosphite is present in the environment, other common reducing agent cannot produce phosphine at the concentration observed in nature [13].…”
Section: Introductionmentioning
confidence: 97%